Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila - Aulia, Niken Ayu; Rondli, Wawan Shokib (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effect of the use of the problem based learning (PBL) model on students' critical thinking skills in the subject of Pancasila education in grade IV at SD 4 Sadang. This research is a quantitative research with an experimental method (pre-experimental design). The population and sample used in this study are all students of grade IV SD 4 Sadang. Data collection instruments and techniques were obtained based on test results. The data was analyzed using the Paired Sample T-Test test through pretest and posttest. The results of the hypothesis test can be seen from the data that have been analyzed with a Sig. (2-tailed) value of 0.000 < 0.05 so that it can be concluded that there is a significant difference between the pretest and posttest results and the N-gain score test results of 0.39 with a moderate category. Thus, the use of problem-based learning models has a positive effect on students' ability to think critically.